The Effects of Different Surgical Approaches on the Perioperative Level of Circulating Tumor Cells in Patients with Non-Small Cell Lung Cancer - Huang, Hong Bo; Ge, Ming Jian (The Thoracic and Cardiovascular Surgeon, 2016)
Background To observe and compare the effects of video-assisted thoracoscopic surgery (VATS) and conventional thoracotomy on the levels of circulating tumor cells (CTCs) in patients with non-small cell lung carcinoma (NSCLC).Methods Seventy-nine patients with a diagnosis of NSCLC were enrolled in the study. Forty-three were treated with VATS and 36 were treated with conventional thoracotomy. Blood samples were collected 3 days prior to surgery (d-3), during surgery (d0), and 3 days after surgery (d3). After epithelial cell adhesion molecule (EpCAM)-labeled immunomagnetic cell enrichment, anti-CK-PE and anti-CD45-FITC fluorescent-labeled monoclonal antibodies were added to sort CTCs. Quantification of CTCs was performed using multiparameter flow cytometry.Results The number of CTCs on d0 was significantly higher than on d-3 (5.730 ± 4.266 vs. 4.142  ± 3.971, p = 0.033) in both groups. There was no significant difference in the change of CTCs from before surgery to during surgery in the VATS and conventional thoracotomy (open) groups (1.363  ± 2.924 vs. 1.500  ± 2.315, p = 0.329). However, the increase in number of CTCs from before surgery to after surgery was significantly lower in the VATS group than in the conventional thoracotomy (open) group (2.181  ± 2.962 vs. 9.666  ± 15.641, p = 0.015). Thirty of the 79 patients tested positive for CTCs before surgery (37.97%). All benign lung disease patients and volunteers tested negative for CTCs.Conclusion A smaller increase in CTCs was seen in patients treated with VATS lobectomy than in patients treated with conventional thoracotomy. This reduction in number of postoperative CTCs may improve long-term survival.
Keywords: thoracoscopy/VATS; lung cancer treatment; inflammation; systemic; tumor